2021
DOI: 10.1002/mnfr.202100253
|View full text |Cite
|
Sign up to set email alerts
|

Daily Dose of Bovine Lactoferrin Prevents Ethanol‐Induced Liver Injury and Death in Male Mice by Regulating Hepatic Alcohol Metabolism and Modulating Gut Microbiota

Abstract: Scope Lactoferrin (Lf) possess a protective potential to liver, but whether it can prevent alcoholic liver injury (ALI) remains unclear. Methods and Results Four groups of male C57BL/6J mice are fed with different diets, namely, AIN‐93G diet for control (CON) and ethanol (EtOH) groups, and AIN‐93G diet with 0.4% and 4% casein replaced by Lf for low‐dose Lf (LLf) and high‐dose Lf (HLf) groups, respectively. ALI is induced by giving 20% ethanol ad libitum combined with four “binges”. Lf can remarkably decrease E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 69 publications
4
30
0
Order By: Relevance
“…Although superoxide is not a strong oxidant, it may be one of the most abundant ROS in the body, and it is a precursor of most other ROS . Thus, superoxide can reflect the total ROS level, at least to a certain extent . In our study, no hydroxyl radical and hydrogen peroxide ESR signals were captured, likely due to their relative low content.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Although superoxide is not a strong oxidant, it may be one of the most abundant ROS in the body, and it is a precursor of most other ROS . Thus, superoxide can reflect the total ROS level, at least to a certain extent . In our study, no hydroxyl radical and hydrogen peroxide ESR signals were captured, likely due to their relative low content.…”
Section: Discussionmentioning
confidence: 66%
“…These results indicated that our animal model of acute ALI is convincing. Unlike LLf, which has more obvious preventive effects in male mice, Lf pretreatment reduced the liver weights and serum transaminase levels in a dose-dependent manner and the differences were significant only in the HLf group. The ameliorating effects of HLf were more obvious on hepatic morphology than LLf, which illustrated that HLf pretreatment had more potent preventive effects of acute ALI for the female mice.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations